DEUS VERSUS OHIRUME DALAM CERPEN KAMIGAMI NO BISHOU: BENTURAN BUDAYA ANTARA BARAT DENGAN JEPANG - Fadli, Zaki Ainul (IZUMI, 2018)
(Title: Deus Versus Ohirume in Kamigami No Bishou: Cultural Clash Between West and Japan) The Kamigami no Bishou short story is one of the most famous Japanese literary works, Akutagawa Ryuunosuke. Kamigami no Bishou was created by Akutagawa in 1922 which tells the meeting of Organtino, a Christian missionary in Japan with an old man who was the embodiment of one of Japan's ancient gods. The purpose of this article is to reveal how the clash of cultures between the West and Japan was reconstructed in Kamigami no Bishou short stories. To achieve this goal, the following steps are taken. First, an explanation of the terms contained in the Kamigami no Bishou Short Story. Second, explained the actions of two figures in the short story that are in opposition to the Greimas model's official scheme because this scheme can make it easier to understand the actions and motivations of the characters. Third, the analysis of one of the short story structural elements is a theme with the aim of understanding the essence and purpose of the entire short story. Fourth, further explanation about the reconstruction of Western versus Japanese cultural clash which is explained by the presentation of binary opposition. After going through all four stages, it was concluded that the reconstruction of cultural clash in Kamigami no Bishou short stories was presented by Akutagawa in a conversation between the Organtino character and the old male character. Through a dialogue centered on Deus versus Ohirume carried out by Organtino figures and old male figures, Akutagawa indirectly wanted to convey the message that Japanese tradition and culture would not be destroyed due to influences from foreign cultures that entered.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor